Prevalence and Determinants of Type 2 Diabetes among the Pulmonary Tuberculosis Cases in Nepal: A Cross Sectional Study - Mahato, R. K.; Laohasiriwong, W.; Koju, R. P. (Kathmandu University Medical Journal, 2021)
Background Since prehistoric time to the earlier 20th century, diabetes was accounted as comorbidity among tuberculosis patients, which is reducing the treatment efficiency. Objective To investigate the prevalence and determinants of type 2 diabetes mellitus among tuberculosis patients in central development region of Nepal. Method An analytical cross-sectional study was conducted by using structured questionnaire. Face to face interview as well as reviewing of the medical records of the tuberculosis cases has been performed during September 2018 - February 2019. The systematic random sampling was applied to select 306 tuberculosis cases. Then the respondents were examined for blood glucose level as well as Glycated haemoglobin (HbA1c) level to identify TB with Diabetes Mellitus. The proportion of respondents with fasting blood glucose level ≥ 126 mg/dl or a random blood glucose ≥ 200 mg/dl was considered as Tuberculosis with Diabetes Mellitus cases. Similarly, haemoglobin A1C ≥ 7% was accessed as amplified risk for tuberculosis. Multiple logistic regression was performed to analyse the factors associated with Tuberculosis with Diabetes Mellitus by using STATA. P value < 0.05 was taken as statistically significant. Result A total of 306 tuberculosis patients were included in the study. The mean ± standard deviation of age of participants was 36.82±15.94 years. The proportion of male slightly exceeded than that of female with a ratio of 1.73:1. The prevalence of TBDM was 17.32% (95% CI: 13.05-21.58) of all diagnosed tuberculosis cases. Our multivariable analysis identified the factors those were associated with TBDM were age ≥ 45 years (adj.OR=3.97, 95% CI 1.81-8.71, p value 0.001), patients residing in the urban areas (adj.OR=9.75, 95% CI 1.99-47.6, p value 0.005), had Body Mass Index (BMI) <18.5 Kg/m2 (adj.OR=3.20, 95% CI 1.58-6.51, p value 0.001), had diastolic blood pressure ≥ 80 mmHg (adj.OR=2.34, 95% CI 1.17-4.66, p value 0.015) and patients who were treated with Cat II and Cat III tuberculosis treatment regimens (adj.OR=2.65, 95% CI 1.22-5.73, p value 0.013). Conclusion The prevalence of type 2 diabetes mellitus among tuberculosis patients was higher than prevalence of diabetes in general population of Nepal and it was higher among male, urban residents, patients with low BMI and the older aged tuberculosis patients.